Clerodane diterpenes from leaves of Casearia sylvestris swartz - Dos Santos, André G. [UNESP]; Perez, Carla C. [UNESP]; Tininis, Aristeu G. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Cavalheiro, Alberto José [UNESP] (FapUNIFESP (SciELO), 2007)
Ethanolic extracts of the leaves of Casearia sylvestris yielded a novel clerodane diterpene, 15-hydroxy-3-cleroden-2-one, together with the known diterpenes (-)-hardwickiic acid, reported for the first time from this species, and casearins B and G, previously isolated from C. sylvestris. The structures of all four compounds were determined by spectrometric analysis. The new clerodane diterpene and (-)-hardwickiic acid contain structural features that are completely different from the highly oxygenated casearins and casearvestrins isolated from C. sylvestris.
Keywords: 15-hydroxy-3-cleroden-2-one; Casearia sylvestris; Clerodane diterpenes